A study on the ballistic impact performance of neat and natural rubber latex-coated unidirectional (non-woven) high strength fabrics / Normala Hassim - Hassim, Normala (Institute of Graduate Studies, UiTM, 2015)
This research explores the application of natural rubber (NR) latex as a thin coating matrix on unidirectional (UD) fabrics for ballistic impact applications. Pre-vulcanised NR lattices were used to coat ballistic fabrics mainly by the single dip method and half dip method. It was found that NR latex changes the frictional aspects among the fibers attached with thin polyethylene film in the coated fabrics. The NR latex film was able to bind the polyethylene film, restrict mobility and share in resisting load applied to the fabric. In particular, an increase in friction was evident from the higher tensile, tearing and puncture resistance of the NR latex coated fabrics in comparison with neat fabrics. In the ballistic impact tests, utilizing several NR latex-coated fabrics in a fabric system increases the ballistic limit as high as 65% in comparisons with all-neat fabric system…